Synthesis of Novel Acetamidobenzanilides Derivatives as Potencial Trypanocidal Agents - Ortellado, Valentin Ignacio (2024)
A simple synthesis of novel N-(2-[N’-acetamidomethyl])benzanilides derivatives from 2-nitrobenzaldehyde in a four steps process is described. The 1H-NMR and 13C-NMR spectra were meticulously analyzed to characterize their structure and it was observed that derivatives with an ortho-substituted phenyl group exhibited detectable atropisomerism. The ADME/toxicity analyses was performed and several of these acetamidobenzanilides were tested in vitro against the epimastigote form of Trypanosoma cruzi, demonstrating significant activity.